Design of a knowledge management system for project management of a Chamber of Commerce in the Caribbean Region in Colombia (2021)
Knowledge management is one of the most important aspects within the organizational development since its function allows the growth and improvement of the company. This research is oriented to the design of a knowledge management system for the Projects Area of a Chamber of Commerce in the Caribbean Region in Colombia (CCC) that allows an adequate use, appropriation, storage and transference of knowledge; understanding the relevance of this aspect for the fulfillment of the mission objects of this institution. A qualitative methodology with a descriptive approach was applied, starting with a documentary review, applying a diagnostic survey and two focus groups to people who directly or indirectly participate in the project phases, to establish the current situation of the Chamber on knowledge management, emphasizing the critical processes that were required to impact in terms of the prioritized components: intellectual capital, ICT, organizational learning, and innovation. Finally, a knowledge management model was selected and adapted for a Chamber of Commerce in the Caribbean Region in Colombia and, subsequently, the system was designed as a tool for knowledge management to facilitate the planning, execution, monitoring and control of projects of the organization. © 2021 Latin American and Caribbean Consortium of Engineering Institutions. All rights reserved.